Statistical inference : a short course - Panik, Michael J. (Hoboken, N.J. : Wiley, 2012)
A concise, easily accessible introduction to descriptive and inferential techniquesStatistical Inference: A Short Course offers a concise presentation of the essentials of basic statistics for readers seeking to acquire a working knowledge of statistical concepts, measures, and procedures. The author conducts tests on the assumption of randomness and normality, provides nonparametric methods when parametric approaches might not work. The book also explores how to determine a confidence interval for a population median while also providing coverage of ratio estimation, randomness, and causality.
6.4 Percentiles of the Standard Normal Distribution and Percentiles of the Random Variable XExercises; Appendix 6.A The Normal Approximation to Binomial Probabilities; 7 Simple Random Sampling and the Sampling Distribution of the Mean; 7.1 Simple Random Sampling; 7.2 The Sampling Distribution of the Mean; 7.3 Comments on the Sampling Distribution of the Mean; 7.4 A Central Limit Theorem; Exercises; Appendix 7.A Using a Table of Random Numbers; Appendix 7.B Assessing Normality via the Normal Probability Plot; Appendix 7.C Randomness, Risk, and Uncertainty; 7.C.1 Introduction to Randomness.
Includes bibliographical references and index.
Print version record.
Keywords: Mathematical statistics -- Testbooks; Mathematical statistics -- Textbooks; MATHEMATICS -- Probability & Statistics -- General; Mathematical statistics; Electronic books; Electronic books